Учебный роман - Уокер Кристин (Бумажные города, 2015)
Экземпляры: Гобгуртская библиотека (20150723) / Инвентарный номер: 201861 / Цена: 287.21 / Сис.шифр: 84(7Сое) / Авт.знак: У 62 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)